2015
DOI: 10.1179/2049396714y.0000000107
|View full text |Cite
|
Sign up to set email alerts
|

Occupational and non-occupational factors associated with work-related injuries among construction workers in the USA

Abstract: Background: Many factors contribute to occupational injuries. However, these factors have been compartmentalized and isolated in most studies. Objective: To examine the relationship between work-related injuries and multiple occupational and nonoccupational factors among construction workers in the USA. Methods: Data from the 1988-2000 National Longitudinal Survey of Youth, 1979 cohort (N512,686) were analyzed. Job exposures and health behaviors were examined and used as independent variables in four multivari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
47
1
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 69 publications
(57 citation statements)
references
References 36 publications
7
47
1
1
Order By: Relevance
“…When other variables are held constant, construction workers working for shorter duration had significantly lower work-related injuries. Similar results were reported by other studies, the risk of injury is associated with occupations of long working hours (Dong, 2005;Dong et al, 2015).…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…When other variables are held constant, construction workers working for shorter duration had significantly lower work-related injuries. Similar results were reported by other studies, the risk of injury is associated with occupations of long working hours (Dong, 2005;Dong et al, 2015).…”
Section: Discussionsupporting
confidence: 81%
“…This finding is similar to a study done in Gondar city, Ethiopia. This might be because of the difference in tasks assigned; males commonly do harder tasks leading to severe injuries (Dong et al, 2015;Adane et al, 2013;Welch et al, 2005). When other variables are held constant, construction workers working for shorter duration had significantly lower work-related injuries.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A majority of the studies reported a positive association between precarious employment and occupational injuries. All of the four studies on multiple job holders indicated that the risk for occupational injuries was higher among these individuals compared to those with only one job (15,16,20,21). Being employed through a subcontractor at the same worksite or staffing agency was also associated with a higher risk of occupational injuries compared to being directly employed by the employer (14,22,23).…”
Section: Dimensions Of Precarious Employment Studied and Their Associmentioning
confidence: 98%
“…Most study groups were general samples of the working population. Four of the studies used a population of blue-collar workers (14)(15)(16)(17) and two of the studies used populations based on health care workers (18,19). The exposure measurements came either from corporate administrations (eg, payrolls), national statistics registers, or were self-reported.…”
Section: Study Characteristicsmentioning
confidence: 99%